2017
DOI: 10.1063/1.4976991
|View full text |Cite
|
Sign up to set email alerts
|

The role of Stern layer in the interplay of dielectric saturation and ion steric effects for the capacitance of graphene in aqueous electrolytes

Abstract: Nano-scale devices continue to challenge our theoretical understanding of microscopic systems. Of particular interest is the characterization of the interface electrochemistry of graphene-based sensors. Typically operated in a regime of high ion concentration and high surface charge density, dielectric saturation and ion crowding become non-negligible at the interface, complicating continuum treatments based upon the Poisson-Boltzmann equation. Using the Poisson-Boltzmann equation, modified with the Bikerman-F… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 66 publications
1
4
0
Order By: Relevance
“…We also investigated the impacts of salt concentration and membrane composition on ion sieving. Prior research has often shown reduced cation or anion selectivity as a result of the diminished range of the surface charge under high-concentration conditions, according to the Poisson–Boltzmann theory. ,, However, we confirmed relatively stable ion sieving performance when the chloride salt concentration was varied between 0.05 and 0.2 M, as illustrated in Figure d. This indicated that selective ion transport based on specific binding interactions with the crown ether molecules was not significantly affected by the ion concentration.…”
Section: Resultssupporting
confidence: 69%
“…We also investigated the impacts of salt concentration and membrane composition on ion sieving. Prior research has often shown reduced cation or anion selectivity as a result of the diminished range of the surface charge under high-concentration conditions, according to the Poisson–Boltzmann theory. ,, However, we confirmed relatively stable ion sieving performance when the chloride salt concentration was varied between 0.05 and 0.2 M, as illustrated in Figure d. This indicated that selective ion transport based on specific binding interactions with the crown ether molecules was not significantly affected by the ion concentration.…”
Section: Resultssupporting
confidence: 69%
“…In addition to repulsive interactions, charged solutes can also lead to an additional dielectric decrement effect by generating strongly oriented hydration layers close to the electrode. Over the years, the electric field strength dependence of the dielectric permittivity has been found to follow a relatively simple analytic function, which is named the Booth model. , This can in principle be used to estimate the interfacial dielectric permittivity and adjust ε ∞ accordingly. , The (M)­DPB approach which explicitly includes the solvent dipoles should also, in principle, be able to correctly account for such surface induced dielectric saturation, but to our knowledge it has not been tested yet for this purpose.…”
Section: Fundamentals Of Implicit Solvationmentioning
confidence: 99%
“…The dependence of ε ( r ) on the density does mean that the Fock operator δscriptG/italicδρ acquires an extra term relative to what was discussed in Section 2.1, namely 262 υε[]ρ()r=18πbold∇false^φboldr2()δερδρboldr. The SCCS model is increasingly being used in ab initio simulations of materials, for example, to model the aqueous electrolyte/solid‐state interfaces relevant in electrochemistry 28,82,264,268–274 . Some of that work points to limitations of the linear dielectric model itself (i.e., a breakdown of the assumption that P ∝ E ), which can result either from high field strength (“dielectric saturation”), 275,276 or else because the rotational response of the water molecules saturates at the electrode interface and consequently the susceptibility is smaller than it is in bulk water 271,272 . Limitations in the linearized Poisson–Boltzmann description of electrolyte effects have also been demonstrated 270–272 …”
Section: Methodsmentioning
confidence: 99%